Visual Communication Models in the Development of ECCE Teaching Materials based on Inkscape Graphics Applications - Darmawan, Ferry; Hakim, Arif; Sevtiany, Venny (KnE Social Sciences, 2023)
The purpose of this study is to empower teachers to create teaching media independently, focusing on visual communication. The study utilizes the unrestricted Inkscape graphics software, providing teachers with a basic understanding of its usage. The research employs development research methods and involves ECCE (Early Childhood Care and Education) teachers at Aisyiyah Kindergartens across West Java as respondents. Development research is employed to produce a specific product and assess its effectiveness. In this case, the aim is to create a visual communication model for early childhood character development. Data collection techniques are conducted through focus group discussions. The findings reveal that teachers’ knowledge of graphics applications is currently limited, and they rarely utilize graphic software to independently create teaching materials, such as storybooks. However, after introducing the basics of using the Inkscape application, teachers exhibit an improved ability to create independent storybooks that align with their desired learning objectives. Moreover, they have the opportunity to involve students and teachers as story characters, fostering emotional connections with the story material. Keywords: Inkscape, children’s storybooks, character development, ECCE